Table of Contents and Introduction - Kathy Miller (Symphony in the Flint Hills, 2010)
Kathy Miller, the first Chair of Symphony in the Flint Hills, Inc. provides an introductory message. This section also includes the 2010 table of contents, information about the major sponsor, UMB Financial Corporation, and "In the Beginning…", a description of the origins of the Symphony in the Flint Hills.
Keywords: Frontmatter; Flint Hills